Trade, Foreign Direct Investment, and R&D Spillovers - Hejazi, Walid; Safarian, A. Edward (Journal of International Business Studies, 1999)
Attempts to measure the spillover effects of multinational enterprises on host countries have generally been cross-sectional and limited to labour productivity in manufacturing for a single country. Recent work in growth theory has measured the extent to which growth in total factor productivity in a country depends not only on domestic R&D capital stocks but also on foreign R&D capital stocks. This paper extends such work by adding foreign direct investment stocks to foreign trade as a channel linking total factor productivity levels between countries. This is done by considering the role of trade and FDI as diffusion channels for G6 R&D to the OECD countries. There are three main results: the coefficient estimates for FDI are higher than those for trade in the standard model; the importance of the trade channel is much reduced once FDI is included; and the overall spillovers increase significantly with the inclusion of FDI.